'Give us a voice!': voice, envoicement, and the politics of 'world music' at WOMAD. Issue 2 (4th May 2022) - Nissen, James
ABSTRACT: During the 1990s and 2000s, 'world music' became a contentious topic in ethnomusicology, with polarised exchanges of 'anxious' and 'celebratory' narratives. Recently, this debate has subsided, and many academics and industry actors have discarded the controversial label. However, attempts to simply bury the discourse are futile because the politics of 'world music' continues to play out within the industry. The problem with the debate was not necessarily the label itself, but the abstract and generalising narratives which simplified discussion of 'world music' production and consumption and excluded the voices of its participants. Applying the concept of 'envoicement' to WOMAD, I show that musicians value this festival as a platform for getting their voices — literal and metaphorical — heard. I argue that, by revealing perspectives which problematise past narratives, an ethnographic approach guided by envoicement could help to nuance understandings of the industry and break through the critical deadlock.